Developing Environmental Awareness and Stewardship by Multimodal Exploration of the Natural World with the Means of Digital Technologies - KENYERES, Miriam (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2025)
Current and acute environmental problems highlight the need to develop educational approaches that can foster both environmental awareness and stewardship. Although environmental education has advanced in recent years and is increasingly supported by policy and legislation, literature continues to point to a gap in terms of transferring knowledge into practice. Considering this gap, the purpose of this article is to propose a conceptual model for developing environmental awareness and stewardship in lower secondary education through the multimodal exploration of the natural world supported by digital technologies. The model, constructed through a systematic synthesis of literature, is based on raising environmental awareness and stewardship through the development of scientific, environmental, and digital competences, along with strengthening the connection with the environment through multimodal and digital exploration. To illustrate the model’s applicability, the article presents an example of a practical activity combining multisensory field exploration with digital tools for documenting, identifying, and interpreting environmental phenomena. This example shows how multimodal experiences, supported by technology and structured classroom reflection, can create meaningful contexts for developing competences relevant to environmental responsibility. The article argues that such competence-based, experiential, and digitally enriched approaches offer promising directions for strengthening environmental awareness and stewardship in everyday-school practice.